Evaluation of a coarse-ground Gafsa rock phosphate in the recuperation of a degraded pasture on a clayey Dark-Red Latosol - Soares, Wilson Vieira; Lobato, Edson; Sousa, Djalma Martinhão Gomes de; Rein, Thomaz Adolpho (Pesquisa Agropecuaria Brasileira, 2000)
A field experiment was conducted on a Dark-Red Latossol (Haplustox) of the Cerrado of the Federal District, Brazil, to evaluate a coarse-ground Gafsa rock phosphate (CGRP) in the recuperation of a Brachiaria decumbens cv. Basilisk pasture. CGRP was compared with triple superphosphate (TSP) at a P2O5 rate of 100 kg ha-1 both applied by broadcasting. A control treatment without P was included together with two other variables: 1) incorporation of the phosphate with a harrow (with and without) and 2) supplementary fertilization (SF) with Ca, Mg, N, K, S and micronutrients (presence and absence). The response to application of phosphates was only observed with the simultaneous application of SF; incorporation was essential for increasing the efficiency of CGRP; with incorporation, the efficiency of CGRP was equal to that of TSP; without incorporation, TSP was significantly superior to CGRP (p< 0.05).